0146 Integrating simulation as mandatory training for community mental health teams. (2nd November 2015) - Piette, Angharad; Humphreys, Rosemary; Kowalski, Christopher; Cross, Sean
Abstract : Background: Simulation has not been widely integrated into the core educational program of mental health trusts. In order to ensure sustainability of simulation in mental health, integration into the routine fabric of healthcare delivery is key. 1 Rigorous measurement of outcomes is essential in ensuring that simulation is adopted by managers and policy makers. We aimed to develop, run and evaluate a number of simulation courses for community mental health staff across NHS mental health trusts ensuring that learning objectives matched the desired outcomes for key stake-holders. Methods: We designed and developed an inter-professional training course for community mental health workers in line with desired learning outcomes at a time of service reorganisation within the trust. We developed questionnaires measuring knowledge and confidence, which were completed before and immediately after the training course. 9 participants from different disciplines took part in semi-structured interviews 2–3 months after the course. Transcripts were analysed using thematic analysis. Results: This course ran on six occasions (n = 49). Knowledge scores increased from ( M = 5.05, SD = 1.56) to ( M = 6.24, SD = 1.60) p = 0 .000, with a large effect size (0.36). There was a statistically significant increase in confidence scores following the training, z = –4.728, p = 0 .000, with a large effect size ( r = 0 .54). Iterative improvements were made to the course as a result of evaluation. Emergent themes from interviews were; learning from others, reflection on ways to improve systems, staff wellbeing and appreciation of the patient perspective. As a result of this evaluation, the course has been embedded as mandatory training within one South London mental health trust. Conclusions: Simulation for community mental health teams can improve knowledge and confidence in clinical skills and was valued by staff at a time of service reconfiguration. By involving stake-holders in course design and demonstrating outcomes, simulation can be embedded within mental health service training and delivery. Reference: Gaba DM. The future vision of simulation in healthcare. Simulat Healthc 2. 2 2007;126–135